2023
DOI: 10.1111/josi.12586
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about sexual harassment among young people? Concluding reflections

Abstract: This article contains concluding reflections for a special issue on sexual harassment among young people. In this concluding article, we reflect on the 14 individual papers in the special issue through three cross‐cutting themes, each with important implications for policy and practice. The themes highlight that (1) attitudes and norms related to sexual harassment are core to its occurrence among young people, (2) the sexual harassment experiences of minority and otherwise hidden youth need to be heard, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Unfortunately, the current findings cannot be used to determine what specific factors should be targeted to stop the harassment from reoccurring. It has been suggested that interventions should address the norms and attitudes that tolerate and promote sexual harassment among young people (Holmqvist Gattario & Lunde, 2023). Previous research (Skoog & Kapetanovic, 2021) and resilience theory (Masten & Barnes, 2018) also suggest that connections with other people and relational support are fundamental for developmental outcomes in challenging or threatening circumstances.…”
Section: Contribution To Research and Practitionersmentioning
confidence: 99%
“…Unfortunately, the current findings cannot be used to determine what specific factors should be targeted to stop the harassment from reoccurring. It has been suggested that interventions should address the norms and attitudes that tolerate and promote sexual harassment among young people (Holmqvist Gattario & Lunde, 2023). Previous research (Skoog & Kapetanovic, 2021) and resilience theory (Masten & Barnes, 2018) also suggest that connections with other people and relational support are fundamental for developmental outcomes in challenging or threatening circumstances.…”
Section: Contribution To Research and Practitionersmentioning
confidence: 99%